Efficacy and safety of dihydroartemisinin-piperaquine - H. Y. Myint (2018)
Dihydroartemisinin-piperaquine, a fixed-dose combination antimalarial, is an inexpensive, safe and highly effective treatment for uncomplicated falciparum or vivax malaria. Efficacy assessed over 28-63 days has consistently exceeded 95% in the treatment of multidrug-resistant falciparum malaria. More than 2600 patients have been treated with this combination in prospective studies, mainly in Southeast Asia. Tolerability was uniformly good, and no serious adverse effects have been identified. The dosing regimen has been simplified from four doses to once daily over 3 days. More information on efficacy in Africa, and more pharmacokinetic and efficacy data in children are needed. © 2007 Royal Society of Tropical Medicine and Hygiene.